Determinants and Growth Impact of Foreign Direct Investment Based on Simultaneous Equation Approach: Evidence in Nigeria - Obakoya, Tolani Timothy; Sokoya, Emmanuel Olusegun (NIU Journal of Humanities, 2018)
Empirical evidences targeted at determining the relationship between FDI and economic growth in Nigeria has drawn inconclusive results.  Most studies used the VAR methodology. For robustness of the interrelationships among determining variables, a more comprehensive and dynamic framework, in the form of a simultaneous equations system of Generalized Method of moments (GMM) technique was adopted. This study attempt to empirically analyze two courses of action: (1) the growth impact of FDI in Nigeria; and (2) FDI determinants in Nigeria. This study treats economic growth and FDI as endogenous variables for the period, 1970 to 2010. The results indicate that there is an endogenous relationship between FDI and economic growth. The GMM test confirms the presence of bi-directional relationship. Therefore, the study suggests that for FDI to be a noteworthy provider to economic growth, Nigeria would do better by focusing on improving infrastructure, human resources, developing local entrepreneurship, creating a stable macroeconomic framework and conditions favourable for productive investments to augment the process of growth. Keywords: Economic growth, FDI, 3SLS and GMM estimates.